Role of Cathepsin K in Normal Joints and in the Development of Arthritis - Salminen-Mankonen, H. J.; Morko, J.; Vuorio, E. (Current Drug Targets, 2007)
Cysteine cathepsins are a large family of proteolytic enzymes active at acidic pH as found in lysosomes. Since its discovery in 1990's, cathepsin K has been shown to be a key enzyme in osteoclastic bone resorption through its activity in the resorption lacuna. Although characteristic to osteoclasts, the expression of cathepsin K has also been observed at other sites in skeleton. Several recent observations have demonstrated up-regulation of cathepsin K in osteoarthritic cartilage and inflamed synovial tissue. As cathepsin K is one of the few extracellular proteolytic enzymes capable of degrading native fibrillar collagen, it may play an important role in the progressive destruction of articular cartilage both in osteoarthritis and in inflammatory arthritides. Also transgenic mouse models have provided evidence supporting the important role of cathepsin K in both groups of arthritides. The aim of this chapter is to review the accumulating evidence for the role of cathepsin K in degradation of articular cartilage regardless of its pathogenic background, and to discuss the potential efficacy of cathepsin K inhibitors to slow down or prevent articular cartilage degradation.
Keywords: inflammation